Mimicking Schizophrenia: Reducing P300b by Minimally Fragmenting Healthy Participants’ Selves Using Immersive Virtual Reality Embodiment - Spanlang, Bernhard; Nierula, Birgit; Haffar, Maud; Debruille, J. Bruno (Frontiers in Human Neuroscience, 2019)
The most robust and clear biological index differentiating persons with schizophrenia from healthy controls is the drastic reduction of the amplitude of their P300b event-related brain potential (ERP). However, the cause of that reduction remains obscure. Nevertheless, the P300b belongs to the family of the late posterior positivities (LPPs) which are closely related to the consciousness of the meaning of the stimulus in the task for the subjects themselves (e.g., the: I am seeing the target stimulus for which I have to respond). The fragmentation of the self, as proposed for schizophrenia, could thus be the cause. If this were true, then P300bs should be somewhat reduced in healthy subjects when their self representations are temporarily and minimally fragmented. To test this hypothesis, subjects were equipped with a head mounted display in which they viewed a virtual room where an avatar was facing them. Stimuli were a frequent green- and a rare red-disk, the oddball stimulus, occurring over the right hand of this avatar. Subjects had to perform a Go/NoGo task, lifting their right hand to the frequent green disk and repressing this action for the oddball red disk. In the syncMove block of trials, the avatar was lifting his right hand synchronously with the subject, disturbing his/her self representation as confirmed by the debriefing session. In the noMove block, the avatar remained immobile. In the classic block, only the red and the green disk were displayed on a monochrome background, neither the room nor the avatar were shown. As predicted, in subjects who had the classically large P300 oddball effect between ERPs to the frequent and those to the rare stimuli, P300bs were found to be smaller in the syncMove block than in the noMove- and the classic-block. Reduced P300bs of schizophrenia could thus be partly due to self fragmentation. Results may also open an avenue of research to the functional significance of LPPs and the content of the consciousness indexed by these potentials.